A comparative study of MPPT and voltage regulator controllers for controlling output voltage in PV applications - Al-Mohammedawi, Ali Jber Mshkil (2019)
The demand for renewable energy sources is more and more increasing on each passing year. Since with the increasing number of the human population, the demand for energy is increasing at an alarming state. Petroleum resources are very limited and in this scenario, renewable energy sources such as solar energy proven to be a much more reliable source of energy generation through solar panel technology but getting the most power out of a solar power system is a complicated task and need advanced digital control system and high efficient algorithms. Many algorithms have been developed for the maximum power point tracking (MPPT) of solar panels. However, most of the algorithms such as artificial intelligence and expert systems need high-end computing systems, which are costly and thus not suitable for normal household utilization. In this research, Perturb and Observe (P&O) algorithm with a PI controller algorithm are selected to enhance the MPPT task over the conventional method. This algorithm needs voltage and a current sensor to sense the power parameters of the panel in real time and generate a small difference in duty cycle called perturbation and a boost converter increase or decrease the voltage level based on the PWM signals until the system reach very close to the maximum power point possible. One flaw of this algorithm is that the system never stops at a fixed power point, rather it perturbs around the maximum power range. For further tuning the maximum power point, voltage amplitude and minimize the distortion, a PI controller will be utilized in this research project. Initial results from the solar panel model using SLG-M 350 module are satisfactory. Furthermore, the model has been tested with boost converter circuit in Simulink with a constant duty cycle. Afterward proposed MPPT+PI algorithm results have been compared with simple MPPT method. It is observed that a PI controller minimize the perturbation effect of the MPPT controller largely, which results in less distorted power curves. Additionally, overall power efficiency is increased in the case of proposed MPPT+PI controller, which is 98.5% as compared to 97.8% efficiency of conventional MPPT controller.